2007
DOI: 10.47102/annals-acadmedsg.v36n5p343
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Chemotherapy in Progressive High-grade Astrocytoma

Abstract: Introduction: Despite aggressive multidisciplinary interventions, patients with high-grade astrocytomas experience tumour progression or recurrence. Treatment for this group of patients remains a formidable challenge. We describe our experience of salvage chemotherapy for these patients. Materials and Methods: A retrospective review of relevant clinical and radiographic information of patients who received at least one cycle of salvage chemotherapy for progressive high-grade astrocytoma at the National Cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
4
1
Order By: Relevance
“…This was followed by cataract (41.9% MSVI, 48.8% LVI/LB, and 9.3% TB). This is unlike the findings from the study in India by Gupta et al [34] as well as others [13,16,20,21,26] in which cataract (50.9%) was the main cause followed by un-corrected refractive error (36%) . In Nigeria, Glaucoma being more prevalent in the south-eastern part of the country dominates the scene.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…This was followed by cataract (41.9% MSVI, 48.8% LVI/LB, and 9.3% TB). This is unlike the findings from the study in India by Gupta et al [34] as well as others [13,16,20,21,26] in which cataract (50.9%) was the main cause followed by un-corrected refractive error (36%) . In Nigeria, Glaucoma being more prevalent in the south-eastern part of the country dominates the scene.…”
Section: Discussioncontrasting
confidence: 88%
“…This is comparable to a hospital based study in Ethiopia [17] and others from Nepal, Sri-Lanka, and India [18][19][20]14,16,9] Similar patterns were observed in Barbados Eye study, Salisbury Ophthalmology assessment study, Rotterdam study and Andhra Pradesh Eye study. [21][22][23][24][25] Age has often been associated with some common causes of blindness like cataract, glaucoma, Age Related Macular Degeneration, (ARMD)and diabetic retinopathy. Lack of comprehensive affordable eye care as part of healthcare package often worsens the problem of the aged which is more profound in the LMICs.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized trials have shown that chemoradiation is beneficial for glioblastoma patients. More research is currently being done to determine the role of chemotherapy for both high-grade and low-grade gliomas [22].…”
Section: Chemotherapymentioning
confidence: 99%
“…This issue includes timely updates of these developments. 5,6 It is clear that there is better overall patient satisfaction and possibly better patient outcomes when patients are treated in a multidisciplinary setting. Few other disciplines demonstrate this philosophy more convincingly than the neuro-oncology model.…”
Section: Neuro-oncology At the Crossroadsmentioning
confidence: 99%